Magnetization Signature of Topological Surface States in a Non‐Symmorphic Superconductor. Issue 39 (8th August 2021) - Kuang, Wenjun; Lopez‐Polin, Guillermo; Lee, Hyungjun; Guinea, Francisco; Whitehead, George; Timokhin, Ivan; Berdyugin, Alexey I.; Kumar, Roshan Krishna; Yazyev, Oleg V.; Walet, Niels; Principi, Alessandro; Geim, Andre K.; et al.
Abstract: Superconductors with nontrivial band structure topology represent a class of materials with unconventional and potentially useful properties. Recent years have seen much success in creating artificial hybrid structures exhibiting the main characteristics of 2D topological superconductors. Yet, bulk materials known to combine inherent superconductivity with nontrivial topology remain scarce, largely because distinguishing their central characteristic—the topological surface states—has proved challenging due to a dominant contribution from the superconducting bulk. In this work, a highly anomalous behavior of surface superconductivity in topologically nontrivial 3D superconductor In2 Bi, where the surface states result from its nontrivial band structure, itself a consequence of the non‐symmorphic crystal symmetry and strong spin–orbit coupling, is reported. In contrast to smoothly decreasing diamagnetic susceptibility above the bulk critical field, H c2, as seen in conventional superconductors, a near‐perfect, Meissner‐like screening of low‐frequency magnetic fields well above H c2 is observed. The enhanced diamagnetism disappears at a new phase transition close to the critical field of surface superconductivity, H c3 . Using theoretical modeling, the anomalous screening is shown to be consistent with modification of surface superconductivity by the topological surface states. The possibility of detecting signatures of the surface states using macroscopic magnetization provides a new tool for the discovery and identification of topological superconductors. Abstract : Highly anomalous surface superconductivity is reported in a non‐symmorphic superconductor, In2 Bi, where the nontrivial band structure results in the existence of topologically protected surface states (TSS). The near‐perfect screening of low‐frequency magnetic fields well above the upper critical field is explained by proximity superconductivity of TSS. Detecting TSS via macroscopic magnetization provides a new tool for identification of topological superconductors.